Role-Play Simulation for Assessing Students’ Creative Skill and Concept Mastery - Nisrina Meta Gamanik; Yayan Sanjaya; Lilit Rusyati (Journal of Science Learning, 2019)
This study treats students by role-play simulation for learning the human circulatory system. Creative skill and concept mastery to be assessed aspects at the end of learning. The method used in this research is the quasi-experimental method. The sample was taken by cluster random sampling technique with the population of students in 8th grade at one of Junior High School in Bandung. The samples in the experimental class n=24 and control class n= 24.the data obtained using the rubric of creative skill consist of process and product. For treatment in experiment class, implemented the role play while for the control class conducted the group discussion. This study aims to examine the effect of role-playing on students’ concept mastery and creative skills. The data result of students’ concept mastery was taken by pretest and posttest. The result of students’ concept mastery was indicated by mean of posttest score in the experimental class, which is implemented the role play is higher than the control class, 79.50 64.00, respectively. Creative skills in the process that will be seen during the implementation of the role play and creative skills in product measured by the scenario of the role play. This research indicated that role play could be implemented in the teaching-learning process. The research findings show that there is a significant effect of role-playing on students’ concept mastery and lead students to be skillfully creative.